THE EFFECT OF GIVING SIRSAK (Annona muricata Linn) ON URIC ACID LEVELS IN PATIENTS WITH GOUT ARTRITIS - andika herlina (Stikes Syedza Saintika Padang, 2020)
ABSTRACT In addition to attacking joint disease, gout arthritis can cause damage to other important organs. One of the herbal treatments for gout can be done with soursop fruit which has anti-oxidant properties which function to reduce the formation of uric acid by inhibiting the production of the xanthine oxidase enzyme. The purpose of this study was to see the effect of offering soursop juice on the uric acid levels of gout sufferers in the Lubuk Begalung Community Health Center Work Area in 2019. This type of research is a quasi-experimental design with a pretest posttest one group design. This research was conducted from August to October. The sampling technique in this study using purposive sampling which can be carried out by 16 people. Collecting data using an observation sheet presenting soursop juice. Data were processed computerized with univariate analysis and bivariate analysis using non-parametric statistical tests, namely the Wilcoxon test.The results showed that the average uric acid level of uric acid patients before being given soursop juice was 9.25 mg / dl, and after being given soursop juice the average uric acid level was 8.56 mg / dl. Based on the statistical test, it was found that the value of p = 0.001 (p ≤ 0.05), which means that there is an effect of offering soursop juice on the uric acid levels of gout arthritis sufferers.Based on these findings, it can be neglected that there is an effect of offering soursop juice on uric acid levels in patients with gout arthritis. It is hoped that the results of this study will be used as input in efforts to improve health services, especially in the management of non-pharmacological actions on gouty arthritis, namely by using soursop juice therapy. Keywords: Soursop Juice, Gouty Arthritis.Reference: 21 (2007-2016)